2002
DOI: 10.1023/a:1021069510797
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The study of the partial oxidation of methane over nickel foils has been carried out over a wide range of reactor temperatures (748± 930 8C) and feed-gas compositions (Ar/CH 4 /O 2 ), ranging from 30 : 29 : 1 to 30 : 12 : 18 cm 3 min ÿ1 at atmospheric pressure. The product formation shows pronounced oscillations. A modi®ed thermocouple was designed to measure the temperature while the interposed nickel foil worked as a catalyst. The oscillations have been attributed to the cyclic reduction and oxidation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 22 publications
1
15
1
Order By: Relevance
“…Studies of the oscillatory behaviour over Ni and Co catalysts revealed that bare chromel-alumel thermocouples could be effective catalysts for methane oxidation, being able to generate oscillatory behaviour in the temperature range from 650 to 730°C [3,8]. When using a thermocouple, precautions were taken to avoid ethane oxidation at its surface.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies of the oscillatory behaviour over Ni and Co catalysts revealed that bare chromel-alumel thermocouples could be effective catalysts for methane oxidation, being able to generate oscillatory behaviour in the temperature range from 650 to 730°C [3,8]. When using a thermocouple, precautions were taken to avoid ethane oxidation at its surface.…”
Section: Methodsmentioning
confidence: 99%
“…The size of the first sample (Co1) was 7 · 3 · 0.75 mm 3 and the size of the second sample (Co2) was 4 · 4 · 0.16 mm 3 . Temperature of Co1 sample was measured by a chromel-alumel thermocouple in a stainless steel shell welded to the sample.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a rule, self oscillations were experimentally observed in the oxidation of methane on bulk nickel catalysts (wires, foils, etc.) under oxygen deficiency conditions [5][6][7][8][9]. The self oscillations had a relaxation character.…”
Section: Introductionmentioning
confidence: 98%
“…A wide class of these reactions is the oxidation of hydrocarbons over transition metals. For instance, self-sustained rate oscillations have been noted in the oxidation of methane, ethane, propane, and butane over supported and unsupported catalysts based on Ni, Co, Pd, Pt, Rh, and Ru [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. The distinctive features of these oscillations are their long periods, ranging from several seconds to tens of minutes, and an induction period before the appearance of the regular oscillations.…”
Section: Introductionmentioning
confidence: 99%